Database and Animation Package of Stellar Evolution Study - Mahaseana Putra; Muhamad Irfan Hakim; Aprilia Wardana; Winardi Sutantyo (Institut Teknologi Bandung, 2006)
The study of stellar evolution is an active major branch in astrophysics. Results from stellar evolution studies are indispensable for studies in some other areas such as chemical evolution of star clusters and galaxies. Recently theoretical/computational studies of stellar evolution often involve large populations of stars ( 106) which need databases of evolution tracks with various realistic parameters (mass, chemical composition, etc). In this paper, an attempt in building such a database and construction of animations of the evolution of stellar internal structures and isochrones which is useful in teaching stellar evolution were described.